Improving Students’ Speaking Skill through Questioning Paper at Poltekkes English Club Meeting - basir, achmad (JUPE : Jurnal Pendidikan Mandala, 2024)
Speaking is a key component of language learning thus students should become proficient speakers in order to respond to enquiries effectively and appropriately. In this situation, teachers must teach students effective speaking techniques in order to help them break the bad habits of word-by-word speech, excessive attention to form, and heavy dictionary use. An efficient method for this is guided speaking, which teaches students how to communicate in a variety of contexts and for a variety of goals. Writing questions on paper with the intention of encouraging self-practice anywhere is known as a questioning paper. It is an alternate method of enhancing their ability to speak. Students use the questioning paper technique to guess and have conversations based on pre-provided questions. It can encourage and support students in having conversations. The researcher conducted the research using a pre-experimental methodology in this research, using a pretest-posttest design for a single group. The group received both pre- and post-tests. Students' speaking abilities are evaluated by a pretest. After the pretest was finished, the resercher gave the students instructions on how to use the questioning paper. A posttest was given as the last step to see how well the treatment was working. The posttest results demonstrate the degree of improvement in the students' speaking abilities. As demonstrated by the students' noticeable increase in speaking after doing the treatment, using the questioning paper method is an excellent way to help students become more skilled speakers.